Paediatric cardiology in South Africa 2016: Quo vadis? - Brown, Stephen; Pepeta, Lungile (SA Heart Journal, 2017)
New drugs and modern interventional strategies have markedly changed the face of paediatric cardiology in recent years. Advances in dealing with childhood cardiac disease have significantly improved outcomes. As a matter of fact, if properly managed, more than 85% of children with congenital heart disease (CHD) can reach adulthood.(1) It is also important to recognise that some of these are preventable and early recognition may markedly alter the course of disease and thus ultimately, the outcome. The main aim of the World Health Organisation’s millennium development goal (MDG) 4 is to reduce the under 5 childhood mortality rate and the world heart federation has shown that not giving attention to cardiovascular disease may undermine all MDGs (www.worldheart.org).